2003
DOI: 10.1002/humu.9138
|View full text |Cite
|
Sign up to set email alerts
|

Oculopharyngeal muscular dystrophy (OPMD) due to a small duplication in the PABPN1 gene

Abstract: Oculopharyngeal muscular dystrophy (OPMD) is a late onset autosomal dominant muscle disorder. The OPMD-locus has been mapped to chromosome 14q11.2-q13. The polyadenylate binding protein nuclear 1 (PABPN1; PABP2) gene has been identified as the mutated gene. The mutation consists of a short meiotically stable trinucleotide repeat in the first exon of PABPN1 gene. We have investigated Dutch OPMD patients from four unrelated families and identified a new mutation in two of the four families. Instead of a repeat e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 16 publications
3
19
0
Order By: Relevance
“…Our data show that (GCG) 7 seems to be very rare in Germany and therefore recessive OPMD is expected to be rare in Germany, too. All (GCN) expansions in OPMD patients reported so far and in our study result in an elongation of a polyalanine tract in the N-terminal domain of PABPN1 [8][9][10][11][12]. Previous works have shown that there is no phenotypic difference between patients with pure GCG expansions and those with additional GCA expansions [8,10,11].All patients of this study also had the typical OPMD phenotype.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…Our data show that (GCG) 7 seems to be very rare in Germany and therefore recessive OPMD is expected to be rare in Germany, too. All (GCN) expansions in OPMD patients reported so far and in our study result in an elongation of a polyalanine tract in the N-terminal domain of PABPN1 [8][9][10][11][12]. Previous works have shown that there is no phenotypic difference between patients with pure GCG expansions and those with additional GCA expansions [8,10,11].All patients of this study also had the typical OPMD phenotype.…”
Section: Discussionsupporting
confidence: 68%
“…al. et al 2002, 1 family and 1 family of this study[11] (GCG) 6 (GCA) 2 (GCG) 2 (GCA)3 GCG 14 AD van der Sluijs et al 2003, 2 families [12] (GCG) 6 (GCA) 3 GCG (GCA) 3 GCG 14 AD Robinson et al 2005 [13], this study, 4 families Polyalanine repeats other than GCG are underlined. AR autosomal recessive; AD autosomal dominant…”
mentioning
confidence: 81%
See 3 more Smart Citations